Demystifying drug dosing in renal dysfunction - Nemecek, Branden D.; Hammond, Drayton A. (American Society of Health-System Pharmacists, 2019)
"Chronic kidney disease affects approximately 30 million adults in the United States. Demystifying Drug Dosing in Renal Dysfunction supports your clinical decision process with guidance on dosage adjustments and monitoring in renal dysfunction for medications, subpopulations, and renal replacement modalities. This time-saving resource provides helpful tips and support for a range of clinical situations, including antiepileptics, cardiovascular disease, co-morbidities associated with chronic kidney disease, critical illness, infectious diseases, oncology, pain management, pediatrics, psychiatry, therapeutic plasma exchange, and transplantation"--Publisher's description